PERFORMANCES OF INSURANCE MARKET IN MONTENEGRO IN CONDITIONS OF FINANCIAL CRISIS - Miljana Novićević; Vladimir Kašćelan; Julija Cerović (Economic Review)
Insurance market of Southeast European countries is characterized by significant changes due to uneven economic growth and development. At markets of developed countries, life insurance premium has the leading position in total insurance premium. Due to insufficient economic development of Montenegro, and inadequate awareness and distrust of citizens, compulsory insurances make the biggest part in the total portfolio of the insurance market in Montenegro. The insurance industry was not fully exposed to crisis and drastic changes have not been expected within this type of industry. The global financial crisis did not have a direct negative impact on the insurance market in Montenegro, but rather the indirect one that may be identified through the decline in purchasing power of citizens, decrease in the lending activity of the banks, and through possible recession. Since the financial markets both in Montenegro and in the region are not sufficiently developed, the insurance companies were not able to invest funds in sophisticated securities and financial derivatives, while the Law on Insurance, on the other hand, limited the companies to invest available monetary assets in risky securities, such as stocks. Insurance development trends primarily depend on economic growth, while strict rules and other regulations dominantly affect the improvement and development of insurance market in every country. Therefore, the control of business of insurance companies, licensed brokers and insurance agents, directing insurance companies to invest free funds into nonrisky forms of property and adequate promotion of insurance activities can provide reduction in negative impacts of economic events, i.e. affect insurance companies so that they realize the best possible business results in this and later period.